The usage and constraints of urban river corridor from a socio-ecological perspective: a systematic review - Lin, Shi; Maruthaveeran, Sreetheran; Mohd Yusof, Mohd Johari (International Association for Landscape Ecology Chapter Germany, 2024)
River corridors, acknowledged as "blue-green infrastructure," have gained increasing attention due to their potential benefits on individual quality of life and social well-being in urban areas. However, there remains a lack of a comprehensive synthesis of evidence through a systematic literature review on the usage and associated constraints of urban river corridors. The paper aims to systematically review those attributes that influence the usage of urban river corridors and to analyse their complex interactions from a socio-ecological perspective. Results comprise an overview of the reviewed literature, including authorship, journal, geographical distribution, sample characteristics, data collection and analysis methods, and critical findings. Fifty-nine peer-reviewed papers published between 2012 and 2023 met the authors' inclusion criteria. The findings highlight the significant influence of individual, social, and physical factors on the usage of urban river corridors. Additionally, time reason also impact users' decisions regarding the usage of urban river corridors. Finally, a conceptual framework was proposed to guide urban planners, designers, and policymakers in enhancing urban river corridors' design and management standards, ultimately creating a sustainable, resilient, and inclusive leisure space catering to diverse needs.